Simulation-Based Exploration with Energyplus as an Energy Efficiency Strategy - Madani, Raihan; Winahyo, Antelas Eka (Kadiri University, 2024)
In countries with tropical or subtropical climates, such as Indonesia, the use of air conditioning is becoming increasingly important for comfort and productivity. However, high energy use in air conditioning systems has significant environmental and economic impacts, including increased greenhouse gas emissions and high operational costs. This research aims to analyze the Energy Consumption Index (ECI) in the Joint Lecture Building, State University of Malang using EnergyPlus software simulation. Research data consists of building data, weather data, building construction data, operating schedules, equipment specifications, and energy usage data. Furthermore, the data analysis technique used ECI calculations based on EnergyPlus software simulation. The research results show that based on the Energy Consumption Index value it is 201,943 kWh/m2/year, but with a savings scenario it becomes 161,964 kWh/m2/year (an increase of 19,797%) so it is classified as efficient. The energy-saving scenario implemented is to replace the Constant Air Volume (CAV) air conditioning system with Variable Air Volume (VAV) and the types of luminaires that were originally fluorescent will be replaced with Light Emitting Diodes (LEDs). The comparison results obtained an energy-saving value of 19,797%. The research results show that using VAV and LEDs technology can increase energy efficiency in the Joint Lecture Building, State University of Malang. The scenario attempts to reduce environmental impact through energy efficiency in commercial buildings and shows that the EnergyPlus simulation method is an effective approach for designing energy savings strategies.